Eleven new species of Amblypsilopus Bigot (Diptera: Dolichopodidae: Sciapodinae) and a key to the species of Madagascar and adjacent islands - Grichanov, Igor Ya. (European Journal of Taxonomy, 2021)
Eleven new species of Amblypsilopus Bigot, 1888 from Madagascar are described and illustrated: A. analamazaotra sp. nov., A. andasibensis sp. nov., A. ankarana sp. nov., A. bairae sp. nov., A. fianarantsoa sp. nov., A. freidbergi sp. nov., A. friedmani sp. nov., A. leonidi sp. nov., A. marinae sp. nov., A. olgae sp. nov., and A. romani sp. nov. New species differ from other representatives of the genus in morphology of male surstylus and cercus mainly and male secondary sexual characters on legs. A. flavus (Vanschuytbroeck, 1962) is redescribed. Presently, ca 60 species of Amblypsilopus are known from the Afrotropical region, and 25 species are found on Madagascar. Western Indian Ocean species are associated with the Indo-Pacific A. pallidicornis group, the Pantropical A. abruptus group and the Madagascan A. stuckenbergi group of species. An identification key to males of 28 species of Madagascar and adjacent islands is compiled for the first time.